Design and reactivity of pentapyridyl metal complexes for ammonia oxidation. Issue 35 (12th April 2019) - Johnson, Samantha I.; Heins, Spencer P.; Klug, Christina M.; Wiedner, Eric S.; Bullock, R. Morris; Raugei, Simone
Abstract : Computational and experimental work shows that Mo pentapyridal complexes can oxidize ammonia in the presence of a chemical mediator and evolve N2 . Abstract : Oxidation of NH3 to N2 by pentapyridyl metal complexes via hydrogen atom abstraction was investigated computationally. Quantum chemical analysis reveals insights on orbital symmetry requirements for efficient NH3 oxidation. The most promising complex, [(PY5)Mo(NH3 )] 2+, was studied experimentally. It shows conversion of NH3 to N2 upon treatment with 2, 4, 6-tri- tert -butylphenoxyl radical.